Why did Uber China fail? Lessons from business model analysis - Yunhan Liu; Do-hoon Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The ride-hailing platform offers the business model of the on-demand business ecosystem in the era of the sharing economy. Platforms such as Uber, Lyft, and DiDi have become popular worldwide and established a strong position in urban transportation. This paper presents a case study analyzing the fierce competition between Uber and DiDi in the Chinese ride-hailing market. First, employing the canvas framework, we show the core characteristics of the business models of the two platforms. Our analysis and comparisons of the strategic positioning and implementation concerning the building blocks of canvas ascribe the success factors of DiDi and the causes of Uber's failure. Although both Uber and DiDi provide similar service offerings for diverse market segments, Uber's mismatches between its strategic focus on the premium segment and service operations proved to be a mistake. On the other hand, DiDi managed its business more efficiently by providing a wide range of service offerings while leveraging the two-sided market. As a result, DiDi has grown successfully as a one-stop transportation platform, which is well-suited to the Chinese market. This study provides meaningful insights into business model innovations in the sharing economy and implications for the evolution of future transportation platforms.
Keywords: 650; canvas model; DiDi Chuxing; ride-hailing platform; sharing economy; Uber China